2020
DOI: 10.3390/jcm9072296
|View full text |Cite
|
Sign up to set email alerts
|

Potential Risk of Other-Cause Mortality Due to Long-Term Androgen Deprivation Therapy in Elderly Patients with Clinically Localized Prostate Cancer Treated with Radiotherapy—A Confirmation Study

Abstract: Androgen deprivation therapy (ADT) is used to improve overall survival (OS) in prostate cancer treatment; however, we encountered that long-term ADT in elderly patients may be related to high other-cause mortality (OCM). This study aimed to confirm the potential risk associated with long-term ADT in elderly patients using a different large cohort. A comparison analysis was conducted between the ≥2- and <2-year ADT groups using open, large data from 1840 patients with clinically localized prostate cancer tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…However, a recent meta-analysis of trials of RT and ADT suggested that patients with Gleason score 9–10 prostate cancer had the greatest benefit from lifelong ADT, whereas the optimal treatment for those with Gleason score 8 prostate cancer might be long-term (but not lifelong) ADT 28 . We also observed that longer-term ADT use by > 2 years increases the occurrence of other causes of mortality in patients aged > 75 years 29 . Meticulous patient selection should be considered to maximize the efficacy of ADT without toxicity.…”
Section: Discussionsupporting
confidence: 56%
“…However, a recent meta-analysis of trials of RT and ADT suggested that patients with Gleason score 9–10 prostate cancer had the greatest benefit from lifelong ADT, whereas the optimal treatment for those with Gleason score 8 prostate cancer might be long-term (but not lifelong) ADT 28 . We also observed that longer-term ADT use by > 2 years increases the occurrence of other causes of mortality in patients aged > 75 years 29 . Meticulous patient selection should be considered to maximize the efficacy of ADT without toxicity.…”
Section: Discussionsupporting
confidence: 56%
“…There were some limitations in this study. The first was from missing important variables, such as comorbidities, androgen deprivation therapy, and access to care, which are very important when studying PCSM and OCM 31,32 . However, these data could not be obtained due to restrictions in permissions to accessing SEER data or such data not existing in the SEER database.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its cancer control advantage, EBRT after RP may cause toxicities. Potentially, some of long-term metabolic toxicities associated with EBRT and/or ADT may result in decreased life expectancy, due to mortality from non-PCa-related causes [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%